If I am asked to write 5 to the second power times 3 to the 5th power in factor form, how would I do that?

Answers

Answer 1
Answer: so 5 to the second power means 5 times itself twice or 5*5 which is noted as 5^2'


times 3 to the fifth power or 3 times itself 5 times or 3*3*3*3*3 which is noted as 3^5


so (5^2)(3^5) is the answer (6075 is the expanded form)
Answer 2
Answer: 5×itself 2x witch would be 25
and 3× itself 5× so this is what it look like 3•3•3•3•3 witch it would be 243

and then 25×243= 6075

Related Questions

Please help with hold page
explain step by step how to arrive at a single rational number to represent the following expression. Show both a written explanation and th related math work for each step
(6h)^8/(6h)^6. can anyone help?​
PLEASE HELP! Im not very good at math
1. Simplify: a^7/a^4A. 1/a^3B. a^3C. -a/a^2D.a^4/a^32. Simplify: r^2s^4t/r^2st^3A. s^3/t^2B. s^3/tC. s^2t^3D. s/t3. Simplify: 3x^6/18xA. 1/6B. x^4/6C. x^5/6D. x^6/64. Identify the property demonstrated 4^3x4^7 = 4^3+7A. Quotient of Powers PropertyB. Power of a Power PropertyC.Power of a Product PropertyD.Product of Powers Property5. Identify the property demonstrated: (a^7)^3 = a^7 x 3A. Power of a Product PropertyB. Quotient of Powers PropertyC. Product of Powers PropertyD. Power of a Power PropertyThank you so much whoever helps!!!

5. Lenny is moving tables in the schoolcafeteria. He places all the tables in a
7 X 4 array. How many tables are in
the cafeteria?​

Answers

The answer would be 28 because u count 7 4 times

Simplify


Rewrite the expression in the form aⁿ


a⋅a⁷=

Answers

a•a^7 = a^8 (add the power (n=1+7=8))

How to solve each system of linear equations ?

Can you help me with #7 & #8

Answers

7) y = 4x + 3
    y = 2x  + 7

y = y 
4x + 3 = 2x + 7
4x - 2x = 7 - 3
2x = 4
x = 4/2
x = 2

To check:
y = 4x + 3                      y = 2x + 7
y = 4(2) + 3                   y = 2(2) + 7
y = 8 + 3                        y = 4 + 7
y = 11                            y = 11

8) y = -3x + 6
    y =  x + 2

y = y
-3x + 6 = x + 2
-3x - x = 2 - 6
-4x = -4
x = -4/-4
x = 1

y = -3x + 6                 y = x + 2
y = -3(1) + 6              y = 1 + 2
y = -3 + 6                  y = 3
y = 3

Select from the drop-down menus to correctly complete each statement. Rectangle ABCD can be mapped onto rectangle EHGF with a translation of followed by a dilation centered at the origin with a scale factor of .

Answers

The answer is 5 units right and the other is 0.5.
5 units right and 0.5 i just took the test

The speed of a falcon is 20 miles per hour less than 3 times the top speed of a cheetah

Answers

60 is ur because 20 × 3≡60

I got another problem on substitution on linear equations... I'm very confused. How do I know which one to start? How do I know what to do? Is there any simple explanations? x -2y =5
3x - 5y =8

Can you help me do this in the simplest way please? I'm kinda struggling to get this concept down... :(

Answers

Don't worry, you just have to get used to these problems! You can do it girl!!

So, it doesn't matter where you start. I would start finding the x in the first equation, like this:

x - 2y = 5
x = 5 - 2y

Which is really easy, isn't it?
Now you know that x is equal to 5 - 2y, so you can substitute the x in the second equation. (You could have done the same solving by y, it doesn't matter :D )

3 ( 5 - 2y ) - 5y = 8

15 - 6y - 5y = 8

- 6y - 5y = 8 - 15

-11y = -7

y = -7/-11 = 7/11

Now you found your y! Let's substitute it in the first equation. (The beginner one, not the one that you worked on) 

x - 2 (7/11) = 5

x - 14/11 = 5

x = 5 + 14/11

x = 69/11

I know you got it now! ;) Otherwise ask me whatever you want!